The Influence of Financial Management on the Financial Management Performance Of MSMEs (Case Study in a Forest Café in Palu City) - Jasmin; Rajindra; Burhanuddin; Haris Abd Kadir (Universitas Muhammadiyah Palu, 2024)
The purpose of this study is to find out the Influence of Financial Management on the Financial Management Performance of MSMEs: A Case Study at the Palu City Forest Cafe. This study uses causal descriptive methods and simple Linear Regression analysis techniques. The sample withdrawal technique is a probality sampling technique or simple random sampling, which is with a sample number of 100 respondents. The results of this study show that the variables of planning, recording, reporting, and evaluation have a positive effect on financial management performance with a significance value of F ? 0.000 < 0.05 Then the planning variable also partially has a positive effect on Financial Management Performance with a significance value of ? 0.006 < 0.05 and the partial planning variable also has a positive influence on Financial Management Performance with a significance value of less than ? 0.001< 0.05 The partial reporting variable also has a positive influence on Financial Management Performance with a significance value less than ? 0.000< 0.05 The partial evaluation variable also has a positive influence on Financial Management Performance with a significance value less than ? 0.00< 0.05.